The development of catalytic performance by coating Pt-Ni on CMI7000 membrane as a cathode of a microbial fuel cell - Cetinkaya, Afsin Y.; Ozdemir, Oguz Kaan; Koroglu, Emre Oguz; Hasimoglu, Aydin; Ozkaya, Bestami (ELSEVIER SCI LTD, 2015)
Performance of cathode materials in microbial fuel cell (MFC) from dairy wastewater has been investigated in laboratory tests. Both cyclic voltammogram experiments and MFC tests showed that Pt-Ni cathode much better than pure Pt cathode. MFC with platinum cathode had the maximum power density of 0.180 Wm(-2) while MFC with Pt: Ni (1:1) cathode produced the maximum power density of 0.637 Wm(-2), even if the mass mixing ratio of Pt is lower in the alloy were used. The highest chemical oxygen demand (COD) removal efficiency was around 82-86% in both systems. The cyclic voltammogram (CV) analyses show that Pt: Ni (1:1) offers higher specific surface area than Pt alone does. X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) results showed that entire Pt: Ni (1:1) alloys can reduce the oxygen easily than pure platinum, even though less precious metal amount. The main outcome of this study is that Pt-Ni, may serve as a alternative catalyst in MFC applications. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Microbial fuel cell; Catalyst; Cathode; Pt; Ni; DAIRY WASTE-WATER; ACTIVATED CARBON; AIR-CATHODE; OXYGEN REDUCTION; POWER-GENERATION; TEMPERATURE; EFFICIENCY; NAFION; BATCH; OXIDE; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels